Características del consumo de piperacilina/tazobactam en los servicios de unidad de cuidados intensivos 2c y unidad de cuidados intermedios 7b del hospital nacional edgardo rebagliati martins - essalud - 2009” - Rodríguez Quito, Iván (2010)
This paper is a study of type descriptive, cross-sectional and retrospective drug consumption, which was designed to determine the characteristics of consumption of Piperacillin/Tazobactam in the services of the Intensive Care Unit (ICU) 2C and Intermediate Care Unit (NICU) 7B of the National Hospital Edgardo Rebagliati Martins - ESSALUD in 2009, by methodology of Defined Daily Doses (DDD/100 beds /day). The male gender had a higher consumption in both services with rates of 63.9% and 72.9% for ICU 2C and NICU 7B respectively. In units the consumption was higher in the service of NICU 7B 2256 than consumption of ICU 2C that was 1476 units. Annual consumption expressed in DDD/100 beds/day of Piperacillin/Tazobactam in the services of ICU 2C and NICU 7B was 5.87 and 8.28 respectively. The trend in consumption in the service of ICU 2C shows a p> 0.05, not statistically significant, the service of NICU 7B had a growing trend, with a value of p <0.05 which indicated a moderate correlation of consumption in function of time. The cost expressed in nuevos soles generated by the consumption of Piperacillin/Tazobactam in the service of ICU 2C was S/. 30 110,4 and in the of NICU 7B S/. 46 022,4. The cost trend in the service of 2C UCI is not statistically significant (p> 0.05), the service of NICU 7B had a growing trend, with a value of p <0.05 which indicated a moderate correlation of cost in function of time